2017
DOI: 10.1515/mmcks-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

How to succeed in the digital age? Monitor the organizational context, identify risks and opportunities, and manage change effectively

Abstract: Abstract. Due to the dynamic and inter-connected internal and external environments of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Also the representativeness of the sample is suggested by the fact that the sample profile matches the statistical population, which is considered a valid argument. (Fonseca and Domingues, 2017).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Also the representativeness of the sample is suggested by the fact that the sample profile matches the statistical population, which is considered a valid argument. (Fonseca and Domingues, 2017).…”
Section: Data Descriptionmentioning
confidence: 99%
“…In the present digital age, organizations are faced with highly global, interconnected, and dynamic environments (Fonseca & Domingues, 2017). The emergence of the phenomenon known as cloud computing represents a fundamental change in the way that are developed, delivered, updated, maintained and paid IT services in modern organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was not possible to use data existing data, a survey was designed to support this quantitative research, taking into consideration the literature review and the research questions. The research instrument adopted a similar structure from those instruments reported in previous studies (Fonseca & Domingues, 2017a, 2017b and it was pre-tested with five automotive industry managers expert. The construct reliability was tested and validated with Cronbach Alpha greater than 0.5, in line with Davis (1964) for groups of 25-50 individuals.…”
Section: Methodsmentioning
confidence: 99%